Oil in Water Nanoemulsions Loaded with Tebuconazole for Populus Wood Protection against White- and Brown-Rot Fungi - Lucía, Alejandro (2021)
Eugenol in water nanoemulsions loaded with tebuconazole appear as a very promising alternative formulations for wood protection against xylophagous fungi that are the main species responsible for different rots in wood structures. The dispersions as prepared and upon dilution (impregnation mixtures) were characterized by the apparent hydrodynamic diameter distribution of the oil droplets loaded with tebuconazole and their long-term stability. The impregnation mixtures were applied on wood of Populus canadensis I-214 clone by using a pressure-vacuum system, and the effectiveness against fungal degradation by Gloeophyllum sepiarium and Pycnoporus sanguineus fungi was determined. The retention of tebuconazole in wood was about 40% of the amount contained in the impregnation mixtures. The results showed that the impregnation process leads to a long-term antifungal protection to the wood, with the mass loss after 16 weeks being reduced more than 10 times in relation to the control (untreated poplar wood) and the reference wood (untreated beech wood).